Prinsip Kesantunan Berbahasa pada Siniar Najwa Shihab “Susahnya Jadi Perempuan” di Kanal Youtube - Ida Bagus Adi Suyoga Puja Perkasa; I Wayan Simpen; Made Sri Satyawati (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
This study aims to describe the realization of politeness in language use in the YouTube podcast Susahnya Jadi Perempuan hosted by Najwa Shihab. The research employs a descriptive qualitative method with a pragmatic approach to analyze how politeness principles are reflected in the participants’ utterances. The theoretical framework is based on Leech’s politeness theory, with particular emphasis on the observance of politeness maxims in spoken interaction. The data consist of utterances taken from the podcast video uploaded on YouTube. Data were collected using the listening method (simak) with the simak libat bebas cakap technique, which allows the researcher to observe naturally occurring conversations without direct involvement. The collected data were then analyzed using the agih method, followed by data reduction and classification according to the relevant politeness maxims. The findings reveal that 24 utterances demonstrate compliance with Leech’s politeness principles. These include the maxim of tact (9 utterances), the maxim of approbation (8 utterances), the maxim of sympathy (3 utterances), and the maxim of modesty (2 utterances). However, no utterances were found to comply with the maxim of generosity. These findings suggest that the podcast emphasizes respectful and appreciative communication in discussing women’s experiences and social issues.